Past Year Technology-Involved Peer Harassment Victimization and Recent Depressive Symptoms and Suicide Ideation Among a National Sample of Youth - Mitchell, Kimberly J. (Journal of interpersonal violence, 2021)
This article aims to better understand the complex role of technology in peer victimization events with recent depressive symptomatology and suicide ideation (SI). Telephone interviews were conducted with a national sample of 791 youth in the United States, aged 10 to 20 years, collected from December 2013 to March 2014. Rates of any peer harassment victimization varied by past month depressive symptomatology and SI —28% of youth with no/low depressive symptomatology reported past year peer harassment as did 43% of youth with high depressive symptomatology without SI, and 66% of youth with SI. When examining the role of technology in peer harassment, youth experiencing any mixed harassment (i.e., those incidents that occurred both in-person and through technology) were almost 4 times more likely to report past month depressive symptoms without SI (RRadj = 3.9, 95% confidence interval [CI] = [1.5, 10.0], p ≤ .01) and 7.5 times (95% CI = [1.9, 28.9], p ≤ .01) more likely to report past month SI compared with youth who had no past year peer harassment. Given the multilayered relationships among these variables, schools, medical, and mental health professionals might screen youth who are involved in higher risk peer victimization situations, for depressive symptoms and SI to improve their access to appropriate mental health services.